Analysis of comorbidities and therapeutic approach for allergic rhinitis in a pediatric population in Spain. Issue 7 (12th September 2013) - Ibáñez, María Dolores; Valero, Antonio Luis; Montoro, Javier; Jauregui, Ignacio; Ferrer, Marta; Dávila, Ignacio; Bartra, Joan; del, Alfonso; Mullol, Joaquim; Sastre, Joaquín
Abstract Background Allergic rhinitis (AR) is the most common chronic disease in children. The main objective of this study was to analyze the comorbidities and therapeutic approaches for AR in a Spanish pediatric population. Methods Children aged 6 to 12 years with AR were included in an observational, cross‐sectional, multicenter study. Results 1, 275 children were recruited from 271 centers. AR was intermittent in 59.5% of cases, persistent in 40.5%, seasonal in 60.7%, and perennial in 39.3% of patients. The most frequent comorbidities were conjunctivitis (53.6%), asthma (49.5%), atopic dermatitis (40%), rhinosinusitis(26.1%), otitis media (23.8%), and adenoid hypertrophy (17.3%). Overall, patients with persistent, moderate or severe, AR were more likely to present comobidities, except for food allergy and urticaria. The most common drugs used for treatment of AR were oral antihistamines(76%), nasal corticosteroids(49%) and a combination of both (45%). Antihistamines and nasal corticosteroids were used on demand (<18 days) in 38 and 41% of patients, respectively; for 18–30 days in 22 and 27%; for 1–3 months in 31 and 29%; and for more than 3 months in 8 and 3%, respectively. Eye drops were used in 32% and specific immunotherapy in 21% of patients. Conclusion Comorbidities are frequent in children with AR, supporting the notion of allergy as a systemic disease. Severity and duration of AR were significantly associated with presence of most of comorbidities. The most common drugs used for AR treatment were oral antihistamines, followed by nasal corticosteroids and a combination of both used on demand.